Techniques and applications of digital watermarking and content protection - Arnold, Michael (Michael Konrad), 1964-; Schmucker, Martin; Wolthusen, Stephen D. (Boston : Artech House, 2003)
This unique easy-to-use software is an integration of tools and simulators that help you solve the most common feedforward predistorted amplifier design equations, including calculating gain and loop balance, optimum coupling ratios, and more. It includes the tools you need everyday, such as a microstrip calculator and parallel coupler designer, to relieve you of lengthy calculations and help you predict the performance of a complex amplifier before all the blocks are together.
Techniques and Applications of Digital Watermarking and Content Protection; Contents vii; Preface xiii; Acknowledgments xv; Chapter 1 Introduction 1; Chapter 2 Digital Watermarking 15; Chapter 3 Applications of digital watermarking 39; Chapter 4 Digital watermarking for still images 55; Chapter 5 Digital watermarking for audio data 75; Chapter 6 Digital watermarking for other media 115; Chapter 7 Attack and benchmarks of digital watermarking systems 147; Chapter 8 Other content protection mechanisms 193; Chapter 9 Integrated content protection solutions 211; Chapter 10 Conclusion 245.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Computer security; Digital watermarking; Data protection; Computer Security; Sécurité informatique; Tatouage numérique.; Protection de l'information (Informatique); digital watermarking; COMPUTERS -- Internet -- Security; COMPUTERS -- Networking -- Security; COMPUTERS -- Security -- General; Computer security; Data protection; Digital watermarking